Uncovering the genetic diversity of Giardia intestinalis in isolates from outbreaks in New Zealand - Paul Ogbuigwe; Patrick J. Biggs; Juan Carlos Garcia-Ramirez; Matthew A. Knox; Anthony Pita; Niluka Velathanthiri; Nigel P. French; David T. S. Hayman (BMC, 2022)
Abstract Background Giardia intestinalis is one of the most common causes of diarrhoea worldwide. Molecular techniques have greatly improved our understanding of the taxonomy and epidemiology of this parasite. Co-infection with mixed (sub-) assemblages has been reported, however, Sanger sequencing is sometimes unable to identify shared subtypes between samples involved in the same epidemiologically linked event, due to samples showing multiple dominant subtypes within the same outbreak. Here, we aimed to use a metabarcoding approach to uncover the genetic diversity within samples from sporadic and outbreak cases of giardiasis to characterise the subtype diversity, and determine if there are common sequences shared by epidemiologically linked cases that are missed by Sanger sequencing. Methods We built a database with 1109 unique glutamate dehydrogenase (gdh) locus sequences covering most of the assemblages of G. intestinalis and used gdh metabarcoding to analyse 16 samples from sporadic and outbreak cases of giardiasis that occurred in New Zealand between 2010 and 2018. Results There is considerable diversity of subtypes of G. intestinalis present in each sample. The utilisation of metabarcoding enabled the identification of shared subtypes between samples from the same outbreak. Multiple variants were identified in 13 of 16 samples, with Assemblage B variants most common, and Assemblages E and A present in mixed infections. Conclusions This study showed that G. intestinalis infections in humans are frequently mixed, with multiple subtypes present in each host. Shared sequences among epidemiologically linked cases not identified through Sanger sequencing were detected. Considering the variation in symptoms observed in cases of giardiasis, and the potential link between symptoms and (sub-) assemblages, the frequency of mixed infections could have implications for our understanding of host-pathogen interactions. Graphical Abstract